Tuning d‐Band Center of Pt by PtCo‐PtSn Heterostructure for Enhanced Oxygen Reduction Reaction Performance. Issue 12 (22nd January 2022) - Chen, Jinli; Qian, Guangfu; Chu, Bingxian; Jiang, Zexing; Tan, Kexin; Luo, Lin; Li, Bin; Yin, Shibin
Abstract: The development of efficient and stable Pt‐based catalysts is significant but challenging for fuel cells. Herein, Sn and Co elements are introduced into Pt to form PtCo‐PtSn/C heterostructure for enhancing the oxygen reduction reaction (ORR). Electrochemical results indicate that it has remarkable ORR intrinsic activity with a high mass activity (1, 158 mA mg –1 Pt) at 0.9 V in HClO4 solution, which is 2.18‐, 6.81‐, and 9.98‐fold higher than that of PtCo/C, PtSn/C, and Pt/C. More importantly, the catalytic activity attenuation for PtCo‐PtSn/C is only 27.4% after 30 000 potential cycles, showing high stability. Furthermore, theoretical calculations reveal that the enhancement is attributed to charge transfer and the unique structure of PtCo‐PtSn/C heterostructure, which regulate the d‐band center of Pt and prevent non‐noble metals from further dissolution. This work thus opens a way to design and prepare highly efficient Pt‐based alloy catalysts for proton exchange membrane fuel cells. Abstract : PtCo‐PtSn/C heterostructure shows excellent activity/high stability and great CO tolerance for the oxygen reduction reaction. The theoretical calculations suggest that this significant enhancement is ascribed to the synergistic interactions between PtCo and PtSn, which governs anchoring of electron‐enriched Pt beneficial to weak bonding strength of O*.